(untitled) (Annals of Medical Research, 2021)
Aim: Late-onset sepsis (LOS) persists to be a crucial reason of morbidity and mortality in preterm infants. Studying the effect of neutrophil-lymphocyte ratio (NLR) value in predicting the LOS episode and relation with the type of the growing microorganism were the aim of this study.Material and Methods: Preterm infants were classified as two groups in accordance with having culture proven LOS during the stay in neonatal intensive care unit. Premature infants with culture proven LOS was defined as study group and infants with no-LOS as control group. Study group is consisting of two subgroups in terms of the growing microorganism type. NLR values were compared within and between the groups.Results: Overall, final analysis were applied to 116 infants. NLR values were raised in the study group during LOS episode (p0.001). NLR value of the Gram-positive sepsis group (Subgroup 1) was significantly higher in comparison to Gram-negative sepsis group (Subgroup 2) (median: 2.4 and 1.8, respectively, p = 0.02). ROC analysis showed that area under the curve (AUC) of NLR was 0.723 (p0.001) and cut-off point optimized for sensitivity of 68% and a specificity of 82% was stated as NLR ≥1.57 for conforming LOS.Conclusions: These findings demonstrated that in preterm infants, NLR values rise for the duration of a LOS episode. We believe that NLR value may be a helpful for the prediction of LOS in preterm infants.